Nobinobi Yomikaki: Teaching Materials For Japanese Reading And Writing Based On 21st Century Skills - Frida Philiyanti; Cut Erra Rismorlita (Jurnal Mamangan, 2023)
This study aims to determine the use of "Nobinobi Yomikaki" teaching materials developed as teaching materials for beginner level reading and writing courses towards the formation of 21st century skills in elementary level students. This is based on the needs for reading and writing teaching materials for first semester students, especially students who have never studied Japanese at all. Efforts to form 21st century skills are the focus as well as the basis for developing teaching materials because the demands of students to be able to survive and perform in the digital world, especially after the Covid-19 pandemic, realize how important non-technical skills are as technical skills. The research method uses a mixed approach, quantitative and qualitative. The quantitative approach was used to measure reading speed, which is a basic literacy skill, while the qualitative approach was used to describe the results of observations of how the use of this teaching material on the formation of 21st century skills. The research population is the 2022 batch of students in the Japanese Language Education Study Program at Universitas Negeri Jakarta, with a sample of 24 people, namely students who have never studied Japanese at all. Based on the observation, it is known that the structure of teaching materials supports the development of 21st century skills, namely the ability to think critically, creatively, communicatively, collaboratively, and succeeds in fostering positive character so that in this digital era students are ready to become part of global citizens or digital citizens. The teaching materials were developed based on research for approximately five years with the help of student contributors, alumni, and native speakers who live in Japan so that it can be said that the teaching materials "Nobinobi Yomikaki" are our original masterpiece with the consideration to form and enhance the 21st-century skills needed